Beyond the Game: How Sports Foster Social Integration among Ukrainian Teenage Refugees - Kölbel, Martin (Current Progress in Arts and Social Studies Research Vol. 10, 2025)
In recent years, the global landscape has witnessed unprecedented humanitarian challenges, particularly with the displacement of populations due to conflict. This research investigates the role of sports programs, both within educational institutions and in community settings, in the subjective integration of Ukrainian war refugees across three host countries—Austria, Germany, and the UK. Through qualitative content analysis of interviews with a sample of 10 refugees, the study explores how participation in sports influences key dimensions of integration, including social connections, belonging, and cultural adaptation. The findings suggest that involvement in sports plays a pivotal role in the integration process, with both school-based and external initiatives offering unique benefits. While sports within educational settings provide structured environments for skill-building and peer interactions, community-based sports initiatives are particularly effective in fostering informal networks and facilitating cross-cultural exchanges. The study highlights the refugees’ resilience and willingness to engage in local communities, noting that active participation in social and recreational activities is essential for their integration into European societies. While country-specific differences in terms of integration exist, it is not the aim of the study to focus on these differences but to elaborate on the individual approaches to integrating adolescent refugees of war. The results emphasize the value of accessible, inclusive sports programs that meet the diverse needs of refugee populations. Additionally, the study underscores the importance of integrating sports initiatives with broader support systems to address the complex challenges faced by refugees. These challenges include language barriers, cultural differences, and the psychological impact of displacement. In conclusion, the research affirms that sports programs can significantly enhance integration, provided they are part of a holistic approach that considers the multifaceted nature of the refugee experience. The study calls for policymakers and practitioners to prioritize the development and implementation of such programs to support the successful integration of refugees into their new communities.